Economics of Catfish Production in Taraba State - P. J. Tsokwa; F. B. Filli; J. L. Gizaki (Darul Yasin Al Sys, 2026)
Catfish production has emerged as a potentially important livelihood and food security enterprise in Taraba State; however, its productivity and sustainability remain shaped by farmer characteristics, input use, and persistent structural constraints. This study examined the economics of catfish production in Taraba State by describing the socioeconomic characteristics of fish farmers, analyzing profitability, identifying the factors influencing production output, and determining the major constraints affecting producers. Primary data were collected from 120 fish farmers across 14 local government areas using purposive sampling. The data were analyzed using descriptive statistics, gross margin analysis, and regression modeling. The findings showed that 65% of the farmers were male, 93% were below 50 years of age, 59% were married, 95% had formal education, 92% had 10 years or less of fish-farming experience, 65% belonged to cooperative societies, and 95% operated with a stocking density of 1,500 or less. Catfish farming was found to be economically viable, with a benefit–cost ratio of 1.51, although feed accounted for 54.42% of variable costs. The multiple regression model produced an R² of 0.889 and a high F-value of 823.110, significant at the 1% level, indicating strong explanatory power. Feed, labor, and water exerted positive and significant effects on output, whereas pond size had a negative and significant effect. The major constraints identified were lack of subsidies, insufficient capital, poor government support, and high feed costs. The study concludes that catfish production in Taraba State is profitable but constrained by high input costs and limited institutional support. These findings imply that targeted subsidies, improved access to credit, policy reforms to reduce production costs, infrastructure development, and farmer training are essential to enhance productivity, strengthen livelihoods, and expand the contribution of aquaculture to the state economy.